2011
DOI: 10.2319/020411-82.1
|View full text |Cite
|
Sign up to set email alerts
|

The effects of application time of a self-etching primer and debonding methods on bracket bond strength

Abstract: Objective: To test the manufacturer's recommendation for the application rubbing time of a selfetching primer (Transbond Plus, 3M Unitek) and to compare the resulting bond strength of a resin composite (Transbond XT, 3M Unitek) in the traditional laboratory tension on all four wings with a simulation of the clinical single-wing lift-off debonding instrument (LODI; 3M Unitek). Materials and Methods: Flattened stainless-steel maxillary incisor orthodontic brackets (Victory Series, 3M Unitek) were bonded to 108 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…Higher ARI values are favorable for avoiding damage to the enamel, as the residue may safely be removed with suitable rotary instruments. In the present study there was higher prevalence of ARI 1 (82%) and 2 (13%) values in all groups, thus detecting a failure in the bonding to enamel, or greater retention of the adhesive material to the bracket, as shown in previous studies (1,24).…”
Section: Discussionsupporting
confidence: 79%
“…Higher ARI values are favorable for avoiding damage to the enamel, as the residue may safely be removed with suitable rotary instruments. In the present study there was higher prevalence of ARI 1 (82%) and 2 (13%) values in all groups, thus detecting a failure in the bonding to enamel, or greater retention of the adhesive material to the bracket, as shown in previous studies (1,24).…”
Section: Discussionsupporting
confidence: 79%
“…The bonded area established in this experiment was equivalent to one-third of one bracket section. Several researchers have described residual adhesive levels after debracketing, at various bond strengths (20)(21)(22)(23). Rikuta et al (24) reported that an area of more than 50% of the SB, which was used to bond the metal bracket onto the tooth surface in a shear test, occurred in 90% of specimens.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, as an orthodontist, we try to find the method which is least painful at debonding stage. Hence, the purpose of the study became to evaluate the best method among the methods which are commonly used for debonding [14,15] determining patients discomfort and amount of adhesive remaining on the enamel surface which, in turn, affects potential enamel damage.…”
Section: Discussionmentioning
confidence: 99%